2014
DOI: 10.1038/srep05000
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating nanopores with diameters of sub-1 nm to 3 nm using multilevel pulse-voltage injection

Abstract: To date, solid-state nanopores have been fabricated primarily through a focused-electronic beam via TEM. For mass production, however, a TEM beam is not suitable and an alternative fabrication method is required. Recently, a simple method for fabricating solid-state nanopores was reported by Kwok, H. et al. and used to fabricate a nanopore (down to 2 nm in size) in a membrane via dielectric breakdown. In the present study, to fabricate smaller nanopores stably—specifically with a diameter of 1 to 2 nm (which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(162 citation statements)
references
References 34 publications
(95 reference statements)
4
155
1
2
Order By: Relevance
“…This unexpected result therefore implies existence of a nanopore unintentionally formed in a membrane. As a concerning possible factor, Yanagi et al 30 reported that dielectric breakdown in the SiN membrane via voltage pulsing induces creation of . The horizontal axis is the pixel distance from center of a particle and the red band in images is the focused area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This unexpected result therefore implies existence of a nanopore unintentionally formed in a membrane. As a concerning possible factor, Yanagi et al 30 reported that dielectric breakdown in the SiN membrane via voltage pulsing induces creation of . The horizontal axis is the pixel distance from center of a particle and the red band in images is the focused area.…”
Section: Resultsmentioning
confidence: 99%
“…30 As the membrane would be subjected to an electrical stress in a similar way under the repeated voltage change for trapping/detrapping of the polymer beads, it is possible that a nanoscale hole was generated during the measurements. It is also probable that the extraneous pore was formed during the fabrication processes.…”
Section: Resultsmentioning
confidence: 99%
“…Short homopolymer single-strand DNA nucleotides have been distinguished in biological nanopores such as those made of hemolysin [2] and MspA [3]. To overcome its short lifetime and to increase nanopore stability and integratability, solid-state nanopores based on silicon nitride (SiN) membrane [4,5] and ultra-thin two-dimensional (2D) layered materials, such as graphene [6][7][8], BN [9,10], and MoS 2 [11], have been fabricated in research laboratories worldwide. Another advantage of a solid-state nanopore is its pore size controllability, which can be achieved by the focused electron beam in a transmission electron microscope (TEM) [12].…”
Section: Introductionmentioning
confidence: 99%
“…21,23,25,27,144,[224][225][226][227]230,233,234 Dielectric breakdown has emerged as a simple, yet extremely flexible and powerful, technique to fabricate nanopores: it requires little more than the usual apparatus used for nanopore sensing and instantly wets the nanopore (contrary to TEM-based methods, for example, where surface contamination poses wetting and other challenges). [235][236][237] In overview, nanopores as small as 1 nm in diameter and $10 nm long can be fabricated with some flexibility in fabrication method. Characterization of nanopores can be done using chargedparticle microscopes and related techniques such as electron tomography and EELS, 219,220,[238][239][240][241] or by much less instrumentally intensive (ionic) conductance-based approaches.…”
Section: Nanofluidic Sample Cellsmentioning
confidence: 99%